Why Do the Cosmic Rays Induce Aging? - Giovanetti, Anna; Tortolici, Flavia; Rufini, Stefano (Frontiers in Physiology, 2020)
The increasing duration of space missions involves a progressively higher exposure of astronauts to cosmic rays, consisting mainly of highly-energetic particles. This radiation interacts along charged particle tracks with biological molecules inducing changes on living material qualitatively different from that observed after irradiation for therapeutic purposes or following nuclear accidents. Charged particles trigger in cells different responses such as oxidative stress, telomere attrition, epigenetic alterations and loss of proteostasis, with consequent mitochondrial dysfunction, genomic instability, metabolism alterations and cell senescence. These cellular phenomena may explain why spending time in space was found to cause the onset of a series of diseases normally related to aging, among these the increase of cancer incidence, immune dysfunction, metabolic alteration, cataract, cardiovascular insufficiency, neuro-degeneration and loss of mass and skeletal muscle strength both in men and in rodent models. Programming longer space flights, in view of future planetary colonization, makes it compelling to study the effects of cosmic rays on aging. Furthermore, these changes that mimic aging but take place more quickly, make space flights an opportunity to study the mechanisms underlying aging. In this short review we describe the main sources of radiation in space and their deleterious effects on the occurrence of aging-related diseases.